YOUTH-GOVERNMENT COLLABORATION IN MARITIME DEVELOPMENT: A PATHWAY TO A SUSTAINABLE JAKARTA - Wibisono, Rizky Bangun (Fakultas Politik Pemerintahan IPDN, 2024)
Abstract This study explores the critical role of young entrepreneurs in advancing Jakarta’s sustainability objectives and bolstering the resilience of its maritime sector. As Jakarta transitions towards a more sustainable urban model, young entrepreneurs are pivotal in developing green technologies that reduce emissions, enhance operational efficiency, and promote eco-friendly practices, aligning closely with the city's sustainability goals. Their innovations directly address environmental challenges such as pollution and climate risks, fostering a green economy while strengthening the sector's capacity to withstand issues like sea-level rise and extreme weather impacts. By collaborating with government entities, these entrepreneurs amplify their influence, co-creating sustainable solutions that reinforce Jakarta’s economic and environmental resilience. This research highlights the transformative potential of youth-driven entrepreneurship as an essential component in achieving a sustainable, resilient, and future-oriented Jakarta. Keywords: Young Participations, Sustainable City, Blue Economy, ESG